Thin-Film Nanocomposite Membranes of Cellulose Nanocrystal/Silver (CNC/Ag) for Removal of Phenol Compounds - Hawash, Samah A.; Enew, Ahmed M.; Mahmoud, Mahmoud H.; Fouda, Safaa R. (Fine Chemical Engineering, 2024)
Bagasse is the sugar cane residue obtained from the sugar industry. It is produced in large quantities and used to make paper because of its fibrous structure. In the present research, sugarcane bagasse (SCB) was chemically treated with HNO3, NaOH, and a bleaching agent to recover 58% of the chemically purified cellulose (CPC), which was subsequently hydrolyzed with H2SO4 to form cellulose nanocrystal (CNC). The capacity of a composite membrane made of cellulose nanocrystal (CNC) enhanced with silver nanoparticles (Ag NPs) to extract phenols from petrochemical effluent was examined. The prepared membrane was examined using a scanning electron microscope (SEM), transmission electron microscopy (TEM), and X-ray diffraction (XRD). The results showed that the white spot on the crystal surface suggested AgNP agglomeration on the CNC surface. The nanocellulose possessed crystallinity indices ranging from 21.9 to 33.1 nm, whereas the silver particles measured 23 and 62 nm. The high separation result of phenol obtained at casting composition of 14% Ag NPs reached 60% at an equilibrium time of 45 min and pH 9. The isothermal and kinetic analysis explained that the rate of adsorption process is the pseudo-second order and followed the Frendlich isotherm models. The CNCs generated using this approach were found to be less agglomerated and more crystalline, indicating a better potential as bio-nanocomposite materials for wastewater treatment.